One-Pot Catalytic Oxidation for Transforming Eugenol to Vanillin Using ZnAl2O4 Catalyst - Damiana Nofita Birhi; Elvina Dhiaul Iftitah; Warsito Warsito; Adzkia Qisthi Ismail (Chemistry Department, The University of Brawijaya, 2021)
In this study, ZnAl2O4 catalyst was synthesized with the capability of transforming eugenol to vanillin through One-Pot Catalytic Oxidation. ZnAl2O4 was synthesized from Zn(CH3COO)2.2H2O and Al2O3 using the wet-impregnation method, and characterized by FTIR, XRD, and SEM. One-Pot Catalytic Oxidation was conducted by heating under reflux at 150oC using nitrobenzene and a certain amount of ZnAl2O4 catalyst (4% and 7%) for 2 and 3 hours of reaction. Catalytic Oxidation is also carried out without catalyst as a comparison. The vanillin product was confirmed by GC and spectral data achieved from UV-Vis, FTIR, and mass spectrometry. The results revealed that transforming eugenol to vanillin using ZnAl2O4 catalyst provides a better selectivity value than without using the catalyst, is 100% for the use of 4% catalyst in 2 hours, while without catalyst gives 88% in 3 hours. In addition, the use of 4% catalyst in 3 hours gives 94% for selectivity of vanillin, and the use of 7% catalyst gives selectivity values at 82% and 85%, respectively for 2 hours and 3 hours. The conversion rate of the use of catalyst and without catalyst gives the perfect rate at 100%, but the use of catalyst produces better vanillin with percent yield at 2.485 for 2 hours, and 3.22% for 3 hours, while without catalyst have percent yield of vanillin at 1.94% for 3 hours.